Análise in silico da sequência deduzida de Mo-CBP3, uma proteína ligante à quitina de Moringa oleifera LAM - Freire, José Ednésio da Cruz (2013)
Moringa oleifera is a tree belonging to the Moringaceae family. This plant is native from India where it is named as drumstick tree. In Brazil M. oleifera was introduced in the 1950’s decade and it is known as moringa. Approximately 40% of the fresh weight of these seeds is formed by proteins, some of which were isolated and characterized as flocculants and antinutritional proteins. In addition, the chitin binding proteins have been identified and isolated, especially among which is the Mo-CBP3, a thermostable glycoprotein of apparent molecular mass of around 14.3 kDa, with potent inhibitory activity against phytopathogenic fungi. In order to characterize the deduced sequence of Mo-CBP3, moringa fruits were collected 65 days after anthesis and their seeds subjected to extraction of total RNA. cDNA synthesis was directed by ‘5’ RACE’-PCR. The PCR products were subcloned into appropriate vectors (pGEM-T Easy) and then introduced into Escherichia coli cloning host TOP10F'. The recombinant plasmids were purified from transformed bacterial cell and subjected to DNA sequencing. The computational analysis of the deduced protein sequence of Mo-CBP3 showed that this protein has an apparent molecular mass of 12.85 kDa and it is unstable in cytoplasmic conditions. It has derived signal sequences, one for the signal peptide with 30 amino acids, and a sequence at the C-terminus of this protein, related to the anchorage to the plasma membrane as well as the endoplasmic reticulum. Moreover, probable sites of O-glycosylation and phosphorylation were identified. One domain related to the lipid transfer functions, reserve and trypsin inhibitors and alpha-amylase was identified following Mo-CBP3, thereby contributing to the understanding of its potent action against phytopathogenic fungi.